2014
DOI: 10.5171/2014.805309
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Nutritional Status and Prevalence of Pneumonia and Diarrhoea among Preschool Children in Kushtia

Abstract: The prevalence of diarrhoea and pneumonia is quite alarming amongst children under 5 years of age who belong to low socioeconomic status. This study was carried out from January to December (2012) in Kushtia, and the total sample were boys (209) and girls (191). Anthropometric measurements were performed by standard methods National Centre for Health Statistics (NCHS). The prevalence of severe underweight, stunting and wasting (≤ -3 SD) were found in the sample data about 11%, 22% and 17% respectively; wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…Similar studies were done in southwest Ethiopia [27] and Ghana [28]. A Cross sectional survey in Bangladesh [29] also reported that children who had history of diarrhoea were at increased risk for ARI. The possible explanation could be that children who have a concomitant illness like diarrhoea may have a lowered immunity, making them more susceptible to a disease like ARI.…”
Section: Discussionsupporting
confidence: 60%
“…Similar studies were done in southwest Ethiopia [27] and Ghana [28]. A Cross sectional survey in Bangladesh [29] also reported that children who had history of diarrhoea were at increased risk for ARI. The possible explanation could be that children who have a concomitant illness like diarrhoea may have a lowered immunity, making them more susceptible to a disease like ARI.…”
Section: Discussionsupporting
confidence: 60%
“…In a study in Bangladesh, among 209 boys and 191 girls with pneumonia and diarrhoea, 17% were found to have SAM. high prevalence of pneumonia (62.72%) and diarrhoea were found in infancy, and in 1-2-year age group [12]. In the present study, SAM was found in 18.5%, which is comparable, even the prevalence of pneumonia (66%) was comparable.…”
Section: Discussionsupporting
confidence: 65%
“…A positive association was noted between the duration of hospital stay and severity of malnutrition. Diarrhoea has short-term effects on nutrition and long-term consequences on the growth of the child [12]. In the present study, the prevalence of diarrhoea was same in SAM and MAM group.…”
Section: Discussionsupporting
confidence: 52%
“…Similar studies have been carried out in southwest Ethiopia and Ghana [ 52 , 53 ]. In addition, a study done in Bangladeshi found that children with a history of diarrhea were more likely to develop ARI [ 54 ]. The reason is children who have a concomitant illness like diarrhea may have a lowered immunity, making them more susceptible to a disease like ARI.…”
Section: Discussionmentioning
confidence: 99%